Subtract the second equation from double the first equation:
2x+6y-2x-(-4y)=0
10y=0
Therefore, y=0. Substituting this into the first equation, we see that:
x+3(0)=3
x=3
Therefore, x=3. The solution to this system is x=3, y=0, or (3, 0).
The first one = 60.3 so it can’t be that one.
the second one = 34.5 so not that one either
the third one = 60.3
and the last one = 28.3
Hello,
We can not divide by 0.
==> x+4.5≠0
==>x≠-4.5
dom f=R\{4.5}
Answer:
-3/4x
Step-by-step explanation:
down 3 left 4 rise/run
You would pay $240 per year, hope this helps